Judging communist crimes in Romania: transnational and global influences - Grosescu, Raluca (International journal of transitional justice, 2017)
In 2016, over 25 years after the fall of the communist regime, the Romanian Supreme Court of Justice convicted for the first time two former military officials for political crimes perpetrated in the 1950s, the harshest repressive period of the previous dictatorship. The verdicts marked a radical break with the prior legal approaches to prosecuting communist crimes in this country inasmuch as international criminal law (ICL) was now employed in order to overcome impunity. This article shows how the current shifts in Romanian jurisprudence have been built upon, and have drawn inspiration from, a recent global convergence towards the use of ICL for addressing the crimes of dictatorial regimes and the obstacles to their prosecution, such as amnesties or statutory limitations. It emphasizes the importance of noncoercive exogenous influences in enabling changes in the Romanian process of dealing with the past.